Issues before 12th Finance Commission: review of vertical and horizontal system of tax sharing - Gurumurthi, S. (2003)
The system of vertical tax devolution from the centre to the states has undergone a major change consequent upon the amendment of the Constitution in August 2000. It will be necessary for the Twelfth Finance Commissionto review the new arrangement. This paper discusses theissues which the Finance Commission may have to examine in the course of such a review. The author looks at the background to the changeover to the new system and discusses issues related to both vertical devolution and horizontal redistribution among the states. - Reproduced.
Keywords: Twelfth Finance Commission; Public finance